THE EVOLUTION OF THE LEGISLATION REGARDING WOOD HARVESTING IN ROMANIA IN THE LAST TWO DECADES - Moga Camelia Elena; Timofte Claudia Simona; Gășpărel Mihai (Natural Resources and Sustainable Development)
This paper analyzes the impact of legislative changes in the last 20 years on wood harvesting activities. The forestry legislation and complementary regulations are presented and analyzed, along with a synthesis of the rights and obligations of business agents and all those who extract/harvest wood. Ministerial Order 1540/2011 (with 5 updates) represents an essential document for regulating forestry exploitation activities in Romania, establishing both the rights and obligations of business operators, agents, and harvesting teams. It contains clear instructions regarding the terms, methods, and periods for the collection, removal, and transport of wood material, aiming to reduce environmental impact and maintain ecological balance. The paper presents the main modifications of this order from 2011 to the present. The two previous orders (from 2002 and 2008) are also mentioned and compared in terms of forest harvesting.